Analysis of Factors Affecting the Behavior of Incidental Deposition in the Community Around the River, Banjarejo Village, Ngadiluwih District, Kediri Regency - Erny Julianingsih; Setyo Budi Susanto; Mika Verrnicia Humairo (Universitas STRADA Indonesia, 2022)
One of the unhealthy lifestyle behaviors is defecating in indiscriminate places such as fields, rice fields, rivers, and other open areas which if left unchecked will pollute the environment, soil, air, and water. In the Banjarejo Village area, they still apply the habit of open defecation (BABS) along the river. From the results of observations that have been made by researchers on October 9, 2020 around the river in the Banjarejo Village area, people are still found defecating around the river. This study aims to analyze the factors that influence the behavior of open defecation in Banjarejo Village, Ngadiluwih District, Kediri Regency. This study uses a quantitative method with an observational research design and uses a cross sectional approach. This research was conducted in Banjarejo Village, Ngadiluwih District, Kediri Regency, a sample of 93 respondents using random sampling technique. Data were collected by questionnaire, bivariate analysis using logistic regression test. The results showed that the variables that had no effect on behavior were economics (p value 0.255 > 0.05) and latrine ownership (p value 0.427 > 0.05) while those that had an influence on behavior were habits (0.00 < 0.05). The behavior of open defecation in Banjarejo village is caused by habitual factors where the habit has become a culture for the surrounding community. This is because some residents do not have their own latrine or latrines that are shared in several houses.